Prevalence, Treatment, and Control Rates of Conventional and Ambulatory Hypertension Across 10 Populations in 3 Continents - Melgarejo, Jesus D.; Maestre, Gladys E.; Thijs, Lutgarde; Asayama, Kei; Boggia, José; Casiglia, Edoardo; Hansen, Tine W.; Imai, Yutaka; Jacobs, Lotte; Jeppesen, Jørgen; Kawecka-Jaszcz, Kalina; Kuznetsova, Tatiana; et al. (Hypertension (Dallas, Tex. 1979), 2017)
Hypertension is a major global health problem, but prevalence rates vary widely among regions. To determine prevalence, treatment, and control rates of hypertension, we measured conventional blood pressure (BP) and 24-hour ambulatory BP in 6546 subjects, aged 40 to 79 years, recruited from 10 community-dwelling cohorts on 3 continents. We determined how between-cohort differences in risk factors and socioeconomic factors influence hypertension rates. The overall prevalence was 49.3% (range between cohorts, 40.0%–86.8%) for conventional hypertension (conventional BP ≥140/90 mm Hg) and 48.7% (35.2%–66.5%) for ambulatory hypertension (ambulatory BP ≥130/80 mm Hg). Treatment and control rates for conventional hypertension were 48.0% (33.5%–74.1%) and 38.6% (10.1%–55.3%) respectively. The corresponding rates for ambulatory hypertension were 48.6% (30.5%–71.9%) and 45.6% (18.6%–64.2%). Among 1677 untreated subjects with conventional hypertension, 35.7% had white coat hypertension (23.5%–56.2%). Masked hypertension (conventional BP <140/90 mm Hg and ambulatory BP ≥130/80 mm Hg) occurred in 16.9% (8.8%–30.5%) of 3320 untreated subjects who were normotensive on conventional measurement. Exclusion of participants with diabetes mellitus, obesity, hypercholesterolemia, or history of cardiovascular complications resulted in a <9% reduction in the conventional and 24-hour ambulatory hypertension rates. Higher social and economic development, measured by the Human Development Index, was associated with lower rates of conventional and ambulatory hypertension. In conclusion, high rates of hypertension in all cohorts examined demonstrate the need for improvements in prevention, treatment, and control. Strategies for the management of hypertension should continue to not only focus on preventable and modifiable risk factors but also consider societal issues.